Complex resistance of spring and winter bread wheat lines to biotic and abiotic stresses - I. F. Lapochkina; N. R. Gainullin; O. A. Baranova; N. M. Kovalenko; L. A. Marchenkova; O. V. Pavlova; O. V. Mitroshina (Вавиловский журнал генетики и селекции)
An original initial material of spring and winter bread wheat with group resistance to stem and leaf rust was developed using new donors of resistance to stem rust: winter soft wheat GT 96/90 (Bulgaria) and accession 119/4-06rw with genetic material of the species Triticum migushovae and (Aegilops speltoides and Secale cereale), respectively, a line of spring wheat 113/00i-4 obtained using the species Ae. triuncialis and T. kiharae, as well as spring accession 145/00i with genetic material of the species Ae. speltoides resistant to leaf rust. The transfer of effective Sr-genes to progeny was monitored using molecular markers. New lines underwent a field assessment of resistance to leaf and stem rust in the epiphytotic development of diseases in the Central Region of the Russian Federation, as well as in the North Caucasus and Western Siberia, and showed high resistance to these pathogens. Fourteen genotypes of spring wheat with group resistance to these diseases and parental forms that participated in the origin of the lines were evaluated for resistance to spot blotch (Cochliobolus sativus) and tan spot (Pyrenophora tritici-repentis) using isolates from Kazakhstan and Omsk in laboratory conditions. A highly resistant parental form of winter soft wheat from “Arsenal” collection 119/4-06rw (wheat-Ae. speltoides-rye hybrid 2n = 42) with group resistance to two spots, four medium-resistant genotypes to both isolates of tan spot from Kazakhstan and Omsk populations of the pathogen, as well as genotypes resistant to the Omsk isolate of P. triticirepentis (parental form 113/00i-4 and lines 1-16i, 6-16i, 9-16i) were isolated. Among the lines of winter wheat, four were identified with group resistance to spot blotch and tan spot. Additionally, the stress resistance of the lines to NaCl salinization and prolonged flooding of seeds with water was evaluated at the early stages of ontogenesis in laboratory conditions. Lines 33-16i, 37-16i, 32-16i and 9-16i showed a high ability to withstand excess moisture. Lines 33-16i, 37-16i, 32-16i and 3-16i were characterized by high salt tolerance, exceeding the average of 49.7 %. Among the winter genotypes, lines were identified with increased resistance to hypoxia (37-19w, 32-19w, 16-19w, 90-19w) and with increased salt tolerance (20-19w, 9-19w, 37-19w, 90-19w), significantly exceeding the standard cv. Moskovskaya 39. The listed lines are of interest as sources of resistance to anaerobic and salt stress, as well as donors of resistance to a group of fungal diseases: leaf and stem rust and tan spot. We attribute the increased level of resistance of the new initial material to the presence of alien translocations in the original parental forms involved in the origin of the lines.